The Influence Of Islamic Work Ethics, Islamic Work Motivation And Islamic Work Environment On Employee Performance Of Banks Of Syariah Indonesia In Banyuwangi City Area - Suprapto, Ribut; Susanti, Nawal Ika; Masitoh, Dewi; Mamlukhah, Mamlukhah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
The purpose of this study was to determine the influence of Islamic work ethics (X1), Islamic work motivation (X2), and Islamic work environment (X3) on employee performance (Y) at BSI Banyuwangi City Region. This study uses a quantitative approach with a questionnaire research type. The sample collection technique uses Nonprobability sampling in the form of saturated sampling . The number of respondents obtained was 60 employees. The analysis tool uses multiple linear regression with the help of SPSS 25 software.Testing using (t-test) shows that Islamic Work Ethics do not have a significant effect on employee performance at BSI Banyuwangi City Area. It has a t count of 0.579 which is smaller than the t table of 1.672 with a significance probability level of 0.565 which is greater than 0.05. Islamic Work Motivation does not have a significant effect on employee performance at BSI Banyuwangi City Area. It has a t count of 0.625 which is smaller than the t table of 1.672 with a significance probability level of 0.535 which is greater than 0.05. Islamic Work Environment has a significant effect on employee performance at BSI Banyuwangi City Area . It has a t count of of 3.802 which is greater than t table 1 , 672 with a significance probability level of 0.000 which is smaller than 0.05. So from the results of the research conducted by the researcher, it can be concluded that together, Islamic Work Ethics, Islamic Work Motivation, and Islamic Work Environment have an effect on Employee Performance at BSI Banyuwangi City Area.